A Review on the Dermatographia and its Effects - S, Yokesh; S, Rithikha; S, Aravindan; K, Maha swetha; G, Gokul raj; C, Divya; S, Harish kannan; P, Praveen kumar; V, Jalaniy; H, Lokesh kumar; G, Sunil kumar; M, Vijay babu; et al. (International Journal of Membrane Science and Technology, 2023)
The urticarial rash known as dermographism, also called dermographism urticaria or urticaria factitia, develops in response to pressure or skin trauma. Inscribing on the skin is the true meaning. A downward force on the skin results in the formation of a linear wave that mimics the pattern of the external force applied. Two to five percent of the population suffer from the very common form of induced or physical urticaria, known as dermatographism. Some people with dermatographism also experience itching symptoms in addition to the reddened hives. This exercise examines the diagnosis and treatment of dermatographism and the role the profession plays in coordinating care and improving patient outcomes.